Heterogeneity of hepatocyte dynamics restores liver architecture after chemical, physical or viral damage - Ruz-Maldonado, Inmaculada; Gonzalez, John T.; Zhang, Hanming; Sun, Jonathan; Bort, Alicia; Kabir, Inamul; Kibbey, Richard G.; Suárez, Yajaira; Greif, Daniel M.; Fernández-Hernando, Carlos (Nature communications, 2024)
Midlobular hepatocytes are proposed to be the most plastic hepatic cell, providing a reservoir for hepatocyte proliferation during homeostasis and regeneration. However, other mechanisms beyond hyperplasia have been little explored and the contribution of other hepatocyte subpopulations to regeneration has been controversial. Thus, re-examining hepatocyte dynamics during regeneration is critical for cell therapy and treatment of liver diseases. Using a mouse model of hepatocyte- and non-hepatocyte- multicolor lineage tracing, we demonstrate that midlobular hepatocytes also undergo hypertrophy in response to chemical, physical, and viral insults. Our study shows that this subpopulation also combats liver impairment after infection with coronavirus. Furthermore, we demonstrate that pericentral hepatocytes also expand in number and size during the repair process and Galectin-9-CD44 pathway may be critical for driving these processes. Notably, we also identified that transdifferentiation and cell fusion during regeneration after severe injury contribute to recover hepatic function. Hepatocytes regenerate the liver after injury, however, the tissue repair mechanisms have been little explored. Here, the authors show that midlobular and pericentral hepatocytes increase their number and size in response to chemical, physical, and viral insults facilitating liver regeneration.